Galling in Actinidia spp. seedlings - Horner, Mary B.; Carroll, Ellena; Wilton, Jayne; Barrett, Will (New Zealand Plant Protection, 2019)
Several Actinidia spp. genotypes exhibit crown gall-like symptoms in both roots and canes. Galls form on roots and pruning wounds of canes. Investigations were undertaken to determine if an Agrobacterium species was responsible for gall formation in the Actinidia spp. material. Macerated galls were plated onto King’s B and various selective Agrobacterium agars, e.g. 1A and Roy & Sasser media. Bacterial isolates were tested by PCR for the presence of tumour-inducing (Ti) plasmids. Isolates that tested positive for the Ti plasmid were subsequently tested for pathogenicity by inoculation onto cut carrot discs, Nicotiana glutinosa and Solanum lycopersicum, and assessed for gall formation. Bacterial isolates that tested positive by PCR for the Ti plasmid were an orange tan colour on selective medium 1A, and clear with a red centre on the Roy & Sasser medium. Galls formed on cut carrots, S. lycopersicum and N. glutinosa after inoculation of Ti-positive bacterial isolates. Initial results indicate that an Agrobacterium species is associated with the formation of galls in Actinidia seedlings. However, biochemical characterisation and confirmation of Koch’s postulates using Actinidia species are needed for verification of this result.